The Elephant Welfare Initiative: a model for advancing evidence‐based zoo animal welfare monitoring, assessment and enhancement. Issue 1 (17th June 2019) - Meehan, C.; Greco, B.; Lynn, B.; Morfeld, K.; Vicino, G.; Orban, D.; Gorsuch, C.; Quick, M.; Ripple, L.; Fournier, K.; Moore, D.
Abstract : The Elephant Welfare Initiative (EWI) is an effort supported by a community of member zoos with the common goal of advancing evidence‐based elephant‐care practices that enhance welfare. The idea for the EWI came about following the completion of a large‐scale North American elephant welfare study, which demonstrated that daily practices, such as social management, enrichment and exercise, play a critical role in improving the welfare of elephants in zoos. In 2014, the Elephant Taxon Advisory Group of the Association of Zoos and Aquariums expressed an interest in building upon the results of this study to support the continued assessment of elephant programmes and implementation of enhanced management practices. The EWI is supported by a web‐based system of software tools and resources. In contrast to traditional record‐keeping systems, the EWI tools provide participants with real‐time analysis as well as zoo‐ and elephant‐level metrics for key welfare indicators and associated management practices. Members' data are pooled to create opportunities for benchmarking, and to leverage the collective efforts of individual organizations to address elephant welfare challenges and generate the data necessary to identify evidence‐based strategies for enhanced outcomes. Future considerations include extending the EWI model to other species in managed settings, and to support transitional programmes for in situ elephant reintroduction efforts. Abstract : The Elephant Welfare Initiative (EWI) is an effort supported by a community of member zoos with the common goal of advancing evidence‐based care practices that enhance welfare. The idea for the EWI came about following the completion of a large‐scale North American elephant welfare study, which demonstrated that daily practices, such as social management, enrichment and exercise, play a critical role in improving the welfare of elephants in zoos. The EWI is supported by a web‐based system of software tools and resources. These tools provide participants with real‐time analysis as well as zoo‐ and elephant‐level metrics for key welfare indicators and associated management practices. Members' data are pooled to create opportunities for benchmarking, and to leverage the collective efforts of individual organizations to address elephant welfare challenges and generate the data necessary to identify evidence‐based strategies for enhanced outcomes. (Image: AWARE Institute, 2019)